1990
DOI: 10.1016/s0022-5347(17)39569-1
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Echinococcosis with Involvement of the Ureter and Testis

Abstract: Alveolar echinococcosis is a rare disease of the liver, and occasionally of the lungs and brain, that is endemic across areas of Central Europe, the Soviet Union and Alaska. We describe a case of alveolar echinococcosis with involvement of the ureter and testis overshadowing the liver manifestation. The unusual presentation and nondemonstrable exposure to the organism caused misinterpretation of the histological findings and an initial misdiagnosis of tuberculosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…2 To best of our knowledge nine papers of scrotal hydatid cysts have been found in medical literature. [1][2][3][4][5][6][7][8][9] Out of these nine case reports, two are testicular hydatid cysts and one is scrotal extension of retroperitoneal hydatid cyst resulting from acute scrotal swelling in a seven years old child. 1,6,8 Remaining six case reports are primary hydatid cysts in scrotum separate from testis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 To best of our knowledge nine papers of scrotal hydatid cysts have been found in medical literature. [1][2][3][4][5][6][7][8][9] Out of these nine case reports, two are testicular hydatid cysts and one is scrotal extension of retroperitoneal hydatid cyst resulting from acute scrotal swelling in a seven years old child. 1,6,8 Remaining six case reports are primary hydatid cysts in scrotum separate from testis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there were only nine reports of hydatid disease involving the scrotum or testis. [1][2][3][4][5][6][7][8][9] We are reporting the tenth case of primary hydatid cysts of left hemiscrotum.…”
Section: Introductionmentioning
confidence: 99%
“…In this unique case report, a 45-year-old male suffered from a painless mass in the scrotum and a cystic cavity of the testis with hydatic cyst was shown macro-and microscopically. On the other hand Strohmaier et al [2] reported an alveolar echinococcosis case with involvement of the ureter and the testis. In this unique testicular alveolar echinococcosis, testis microscopically revealed granulomatous inflammation with small cysts, which contained caseous necrosis misdiagnosed as tuberculosis at the first evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Central Europe usually fox and rarely cats are the sources of the alveolar type of the disease [2]. In each instance, cysts are acquired by humans who accidentally eat the eggs excreted in the feces of dogs or alternate feral hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Echinococcosis or hydatid disease in humans is caused by larval forms of cestode Echinococcus granulosus and rarely by E. multilocularis [1]. It's a cyclozoonotic parasitic infection with the liver (45%-75%) and the lung (10%-50%) being the most commonly involved organs [2].…”
Section: Introductionmentioning
confidence: 99%